Credibility of the cadastral data on land use and the methodology for their verification and update. (March 2021) - Cienciała, Agnieszka; Sobolewska-Mikulska, Katarzyna; Sobura, Szymon
Highlights: Land use constitutes one of the key cadastral data, being, among others, the basis for tax calculation. The main rationale for sustainable management of cities is the regular and thorough verification of the credibility of data. In many cases, such data are unreliable and outdated, causing significant tax losses in the budget of local government units over the years. Modern geospatial technologies may facilitate regular verification of such data, providing the ground for the need of their update and therefore influencing future economic benefits for the local government units. Abstract: Land use constitutes a key form of cadastral data. The term 'land use' varies across countries and there are many different solutions for registering such data. However, the importance of information on the type of land use has been repeatedly emphasised in the literature on the subject in Poland and other countries. It serves as the basis for taxation, supports urban planning, influences real property values and affects land management procedures. The main rationale behind sustainable management of cities is the systematic and comprehensive credibility verification of the data being the basis for tax calculation – the information on land use contained in the cadastre. The research conducted by the authors revealed that, in many cases, such data are unreliable and outdated, causing significant tax losses in the budget of local government units over the years. However, modern geospatial technologies may facilitate regular verification of such data, providing the ground for the need of their update and therefore reaping future economic benefits for local government units. The results of the research (performed with Phantom 3 Advanced) showed the usefulness of unmanned aerial vehicles (UAVs) as a suitable technology for acquiring high-resolution orthophotomap (in the analysed case with a GSD of 3 cm) providing data on the scope of each land use, ensuring the accuracy higher than demanded (≤0.5 m). The obtained spatial resolution of the orthophotomap did not exceed 8 cm. This publication presents an overview of the regulations and existing literature on the subject, the findings of research on the reliability of cadastral data on land use and the most problematic issues in the field. Model methodology for verifying cadastral data on land use by integrating surveying and photogrammetric materials will also be discussed.